Counteracting subliminal cues that threaten national identity. (22nd June 2021) - van Breen, Jolien A.; de Lemus, Soledad; Spears, Russell; Kuppens, Toon
Abstract : In spite of their subtle nature, subliminal cues of group devaluation can have profound effects on members of targeted groups. Across three studies, we examine factors that allow people to counteract subliminal cues of group devaluation. We do this in the context of Spanish–German intergroup relations following the 2008 financial crisis. Throughout the crisis, narratives in politics and the media have drawn on national stereotypes to legitimize the economic situation in Spain. We argue that this represents a threat to our Spanish participants and that exposure to subliminal cues that reflect this threat will trigger responses that counteract this threat. Indeed, results showed that when subliminal associations legitimize the disadvantage faced by the group, our Spanish participants reversed the subliminal associations to which they were exposed. These findings show that Spanish participants are able to counteract the devaluation of their national in‐group, even when that devaluation occurs outside of conscious awareness.